The American Challenge: Terrorists, Detainees, Treaties, and Torture-Responses to the Rule of Law, 2001-2008 - Christol, Carl Q. (Hamilton Books, 2009)
This sequel to Carl Q. Christol's International Law and U.S. Foreign Policy (2nd Revised Edition, 2006) is based on original sources, such as the Constitution, treaties, statutes including the Detainee Treatment Act of 2005 and the Military Commissions Act of 2006, critical Supreme Court decisions, all relevant Department of Justice memorandums that have been released to the public, and the wide-ranging public writings of scholars and members of the professional estate. Christol emphasizes the significance of the constitutional concept of separation of powers, pointing to the efforts of the Executive branch to call upon the Commander-in-Chief and war powers during what has been referred to as 'the war on terrorism.' He draws attention to the growing authority of 'military law' and, in the contest between the three branches of government, Christol emphasizes the roles of Congress and the Courts in the protection of civil and political rights and liberties.